2005
DOI: 10.1051/animres:2005001
|View full text |Cite
|
Sign up to set email alerts
|

Comparative description of growth, fat deposition, carcass and meat quality characteristics of Basque and Large White pigs

Abstract: -Characteristics of growth, fat deposition, carcass and meat quality of pigs from the Basque Black Pied breed were described and compared with those of Large White pigs. Four pens, two per breed, of eleven pigs born during the same two week period, were simultaneously fattened and slaughtered, under the same conditions. The experiment was carried out over a fixed duration (124 days) and slaughter was carried out at a fixed average age (202 days). Basque pigs showed lower growth and feed efficiency and higher b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
41
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 11 publications
17
41
2
10
Order By: Relevance
“…The higher IMF proportion of the B pigs (3.93% v. 2.23% for B and LW, P < 0.001) was in accordance with their higher body fatness (Lebret et al, 2014). It is also in agreement with the results reported for IMF proportion (Labroue et al, 2000) or marbling density (Alfonso et al, 2005) in this breed, and confirms the great potential of local pig breeds for IMF deposition (Lebret, 2008;Pugliese and Sirtori, 2012). In agreement with the present results, lower LM collagen concentrations and higher proportion of non-reducible, thermo-resistant collagen cross-links were found in local Casertana compared with LW pigs at 330 days of age (Maiorano et al, 2013).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The higher IMF proportion of the B pigs (3.93% v. 2.23% for B and LW, P < 0.001) was in accordance with their higher body fatness (Lebret et al, 2014). It is also in agreement with the results reported for IMF proportion (Labroue et al, 2000) or marbling density (Alfonso et al, 2005) in this breed, and confirms the great potential of local pig breeds for IMF deposition (Lebret, 2008;Pugliese and Sirtori, 2012). In agreement with the present results, lower LM collagen concentrations and higher proportion of non-reducible, thermo-resistant collagen cross-links were found in local Casertana compared with LW pigs at 330 days of age (Maiorano et al, 2013).…”
Section: Resultssupporting
confidence: 90%
“…The higher eating quality of meat from B pigs is in agreement with breed differences found in almost all pork quality indicators under study that are associated with sensory quality -that is, the higher pH1 and pHu values and IMF concentration and the lower water losses, breaking energy and shear force (De Vol et al, 1988;Monin, 1988; Breed, production system and meat quality in pigs Huff-Lonergan et al, 2002;Lebret, 2009). Our study confirms the higher scores for redness, marbling, tenderness, juiciness and flavour of meat from B compared with LW pigs found by Labroue et al (2000) and Alfonso et al (2005), and are in line with the high eating quality reported in local compared with conventional pig breeds (Labroue et al, 2000 in Gascon v. LW pigs;Bonneau and Lebret, 2010 for review).…”
Section: Meat Quality Indicatorssupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with the recent findings of Pietrolà et al (2006), CT pigs had lower (P<0.05) average daily gain (ADG) than the other two genotypes. The lower growth rate of the unimproved breed confirms the findings found in other Italian (Acciaioli et al, 2002;Filetti et al, 2003;Franci et al, 2003) and European (Legault et al, 1996;Serra et al, 1998;Alfonso et al, 2005) native breeds.…”
Section: Growth and Slaughter Performancesupporting
confidence: 85%